Analysis of Islamic Law Sources on Positive Law in Handling Cases of Domestic Violence at the Ternate Police - Masri, Rahman; Situmorang, Jubair; Alimuddin, Harwis (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the integration between Islamic law and positive law in handling Domestic Violence (KDRT) cases at Ternate Police Department. The background of the research is based on the high number of domestic violence cases in Ternate and the need for a legal approach adaptive to the local socio-religious context. The research problem focuses on how the integration between these two legal systems is applied in practice. This study employs empirical legal research methods with juridical-empirical, normative, sociological, and philosophical approaches. Data collection techniques include interviews, observation, documentation, and literature review. The findings reveal that the Ternate Police Department implements a hybrid justice approach, combining positive law enforcement and settlement based on Islamic islah values. This approach demonstrates efforts to adapt national law to the social realities of Ternate society without neglecting the protection of victims' rights. The main obstacles are cultural patriarchal pressure and the victims’ economic dependency; however, collaboration with social institutions strengthens the effectiveness of case handling. This study concludes that the integration of Islamic law and positive law in Ternate can serve as an alternative model for addressing domestic violence in culturally religious regions.